(untitled) (Research, Society and Development, 2020)
The present study aimed to investigate in the literature the current knowledge about the relationship between obesity and breast cancer. This is an integrative review carried out by searching for original articles that related obesity and breast cancer, published in the last five years and indexed to the PubMed, Scopus and Web of Science databases. Of the total recovered, 5 articles were included for full reading because they correspond to the eligibility criteria. It was observed that 40% (n = 2) of the studies pointed to the influence of the metabolic aspects characteristic of the obese, on the etiology of breast cancer, as well as, 20% (n = 1) of the studies demonstrated that altered levels of adiponectin and leptin are associated with the pathogenesis of the neoplasia in question. Despite this, a quote did not observe the effect of obesity on the status of chemotherapy patients. It was concluded that the literature points to the relationship between obesity and breast cancer, although the studies are still considered to be poorly understood.